Magma Evolution of Lasem and Senjong Volcanic Complex: High-K Magmatism in Sunda Arc, Indonesia - Haryo Edi Wibowo; Agung Harijoko; Mradipta Lintang Alifcanta Moktikanana; Mohammad Yazid Abdillah (Indonesian Journal on Geoscience, 2022)
DOI:10.17014/ijog.9.1.131-145Lasem and Senjong Volcanic Complex (LSVC) is one of four Quaternary volcanic complexes with high-K magmatism distributed in the northern coast of Central Java. This research aims to understand the magmatic evolution of the volcanic complex. Morphostratigraphy analysis and field observation show twelve pyroclastic density flow units in Lasem Volcano, distributed mainly in the northern to eastern flanks, but minor occurrences in the southern and western flanks. Meanwhile, nine lava flow units of Lasem are concentrated on the south flank of the volcano. Lasem stratovolcano is attributed to four lava domes distributed on the northern and southern flanks. Senjong Volcano comprises one lava flow and four lava domes. Rocks of LSVC are composed of plagioclase, K-feldspar, hornblende, clinopyroxene, and opaque minerals embedded in the groundmass of volcanic glass and microlite. These calc-alkaline rocks range from basaltic trachyandesite to trachyte in composition. The magma of LSVC can further be grouped into High K/Rb and Low K/Rb types, which dominate the Lasem and Senjong Volcano products, respectively. These two magma types consistently show divergent trends in K/Rb and Rb/Nb plots against increasing silica, indicating distinct differentiation processes of similar magma source.